Jumping into the deep-end: results from a pilot impact evaluation of a community-based aquatic exercise program - Barker, A.; Talevski, J.; Morello, R.; Nolan, G.; de Silva, R.; Briggs, Andrew (2015)
This multi-center quasi-experimental pilot study aimed to evaluate changes in pain, joint stiffness, physical function, and quality of life over 12 weeks in adults with musculoskeletal conditions attending ‘Waves’ aquatic exercise classes. A total of 109 adults (mean age, 65.2 years; range, 24–93 years) with musculoskeletal conditions were recruited across 18 Australian community aquatic centers. The intervention is a peer-led, 45 min, weekly aquatic exercise class including aerobic, strength, flexibility, and balance exercises (n = 67). The study also included a control group of people not participating in Waves or other formal exercise (n = 42). Outcomes were measured using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and EuroQoL five dimensions survey (EQ-5D) at baseline and 12 weeks. Satisfaction with Waves classes was also measured at 12 weeks. Eighty two participants (43 Waves and 39 control) completed the study protocol and were included in the analysis. High levels of satisfaction with classes were reported by Waves participants. Over 90 % of participants reported Waves classes were enjoyable and would recommend classes to others. Waves participants demonstrated improvements in WOMAC and EQ-5D scores however between-group differences did not reach statistical significance. Peer-led aquatic exercise classes appear to improve pain, joint stiffness, physical function and quality of life for people with musculoskeletal conditions. The diverse study sample is likely to have limited the power to detect significant changes in outcomes. Larger studies with an adequate follow-up period are needed to confirm effects.